Back Cover: Advanced Real‐Time Process Analytics for Multistep Synthesis in Continuous Flow (Angew. Chem. Int. Ed. 15/2021). Issue 15 (8th March 2021) - Sagmeister, Peter; Lebl, René; Castillo, Ismael; Rehrl, Jakob; Kruisz, Julia; Sipek, Martin; Horn, Martin; Sacher, Stephan; Cantillo, David; Williams, Jason D.; Kappe, C. Oliver
Abstract : Advanced process analytics are becoming an increasingly important part of continuous flow chemistry. In their Research Article on page 8139, Jason D. Williams, C. Oliver Kappe and co‐workers describe the use of four different process analytical technologies, controlled by one central system, in a multistep continuous flow process. Advanced data processing methods, including artificial intelligence, are used to accurately quantify up to nine process species in real time, toward self‐optimization and model predictive control applications.